The impact of talent management towards digital leadership competencies through learning organization: an exploratory analysis in state-owned enterprises in Indonesia - Tonda Priyanto; Agus Heruanto Hadna; Indrayanti; Muhadjir Darwin (Cogent Business & Management)
This research investigates the implementation of talent management in Indonesian state-owned enterprises to improve digital leadership competency. More specifically, it examines learning organization as a mediator between talent management variable and digital leadership. Purposive random sampling is used to gather data from respondents from 26 state-owned enterprises representing ten industries in Indonesia. The originality of this research is the exploration of the influence between talent management, learning organization, and digital leadership competency, which has never been examined. This study is the first attempt to measure the impact of talent management and learning organizations on digital leadership competencies based on empirical data in Indonesian government-owned companies. This research identifies that talent management has a positive and significant influence on learning organizations, and learning organizations have a positive and considerable influence on digital leadership competencies. The impact of talent management on digital leadership competencies, which the learning organization fully mediates, shows a positive and meaningful statistical relationship. However, the hypothesis directly testing the influence between talent management and digital leadership competencies has a small relationship. Based on these results, this study recommends that organizations integrate and align talent management and learning organization strategies to foster the growth of talents with solid digital abilities.